2017
DOI: 10.1016/j.snb.2017.06.155
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor-type SnO2-based NO2 sensors operated at room temperature under UV-light irradiation

Abstract: NO2-sensing properties of typical oxide (SnO2, In2O3, or WO3)-based semiconductor gas sensors were measured at 30°C with and without UV-light irradiation (main wavelength: 365 nm), and effects of noble-metal (Pd or Pt) loading, UV-light intensity (0-134 mW cm −2) and relative humidity in target gas (0-80%RH) on their NO2-sensing properties were investigated in this study. The UV-light irradiation effectively reduced the resistances of all sensors, enhanced their NO2 responses in some cases, and tended to accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 47 publications
0
39
0
1
Order By: Relevance
“…1318 An additional second constituent that acts as the energetic material enhances the degree of the redox reaction with the target gases. Hyodo et al 14 reported the gas sensing characteristics of Pd-doped SnO 2 at room temperature for NO 2 under UV light. For a UV light of 7 mW cm –2 , 0.05Pd-doped SnO 2 exhibited an enhanced response toward the gas.…”
Section: Introductionmentioning
confidence: 99%
“…1318 An additional second constituent that acts as the energetic material enhances the degree of the redox reaction with the target gases. Hyodo et al 14 reported the gas sensing characteristics of Pd-doped SnO 2 at room temperature for NO 2 under UV light. For a UV light of 7 mW cm –2 , 0.05Pd-doped SnO 2 exhibited an enhanced response toward the gas.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, thermal‐activated and ultraviolet (UV)‐light driven gas sensors stand for two complementary chemiresistive‐type gas sensing technologies . Even though the thermal‐driven type provided high sensitivity with a rapid response/recovery speed, it would suffer from high operating temperature .…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the power consumption of metal oxide gas sensors, the effective strategies, mainly include surface modification, additive doping and light activation (Wang et al, 2017;Xu and Ho, 2017;Zhu and Zeng, 2017). Most of the publications dealing with the gas sensor properties of semiconductor materials under illumination discussed the effects observed under UV light (Saura, 1994;Mishra et al, 2004;Malagu et al, 2005;De Lacy Costello et al, 2008;Peng et al, 2008Peng et al, , 2009Prades et al, 2009a,b;Carotta et al, 2011;Wang et al, 2011;Cui et al, 2013;Wagner et al, 2013;Klaus et al, 2015;Ilin et al, 2016;Nakate et al, 2016;Saboor et al, 2016;Trawka et al, 2016;Wongrat et al, 2016;Da Silva et al, 2017;Espid and Taghipour, 2017;Hsu et al, 2017;Hyodo et al, 2017;Wu et al, 2018). UV radiation with an energy exceeding the width of the band gap generates electron-hole pairs and thus increases conductivity.…”
Section: Introductionmentioning
confidence: 99%